(untitled) (Revista Argentina de Cirugía, 2022)
Background: pancreatoduodenectomy is the treatment of choice for periampullary tumors. The first laparoscopic Whipple was performed by Gagner in 1994. However, the extension of the dissection, the need to perform multiple anas- tomoses in reconstructive phase and the length of the procedure were the main reasons that discouraged surgeons. However in recent years the laparoscopic Whipple procedure has emerged as a therapeutic alternative with encoura- ging results in selected patients. Aim: present the initial experience with laparoscopic Whipple procedure and the technical aspects of the approach. Setting: hepatobiliopancreatic surgery sector of the Hospital Italiano de Buenos Aires. Design: prospective, observational. Population: 28 patients undergoing Whipple procedure between December 2010 and June 2011, eight of them were addressed by laparoscopy and they are the group that we analyzed. Method: we analyzed patients approached laparoscopically with intent resection. Operative time, intra and postop- erative complications, length of stay, conversion rate, applicability of the approach and the mortality rate of laparosco- pic and global pancreatoduodenectomy were the variables that we analyzed. Results: mean operative time was 470 minutes. The conversion rate to open surgery was 25%, and the applica- bility of the approach was 28%. There were 33% major complications. The average length of stay was 8 days. Conclusions: laparoscopic Whipple procedure is an alternative laparoscopic technique feasible in selected patients carry periampullary tumors, the initial selection of patients has led to a population of more easily resectable disease, but more difficult to rebuild.